Price determinant model of serviced apartment in Johor Bahru city centre - Azni Raihan Aziz, 1990-, author; Ibrahim @ Atan Sipan, supervisor; Fakulti Geoinformasi dan Harta Tanah (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains (Harta Tanah)) - Universiti Teknologi Malaysia, 2017